Upregulation of Cortical Renin and Downregulation of Medullary (Pro)Renin Receptor in Unilateral Ureteral Obstruction - Figueroa, Stefanny M.; Lozano, Mauricio; Lobos, Carolina; Hennrikus, Matthew T.; Gonzalez, Alexis A.; Amador, Cristián A. (Frontiers in Pharmacology, 2019)
Chronic kidney disease (CKD) is characterized by renal dysfunction, which is a common feature of other major diseases, such as hypertension and diabetes. Unilateral ureteral obstruction (UUO) has been used as a model of CKD in experimental animals and consists of total obstruction of one kidney ureter. The UUO decreases renal blood flow, which promotes the synthesis of renin in the juxtaglomerular apparatus, the first step in renin-angiotensin system (RAS) cascade. RAS induces inflammation and remodeling, along with reduced renal function. However, it remains unknown whether intrarenal RAS (iRAS) is activated in early stages of CKD. Our objective was to characterize different iRAS components in the renal cortex and in the medulla in an early phase of UUO. Male C57BL/6 mice (8-12 weeks old) were subjected to UUO in the left kidney, or to sham surgery, and were euthanized after 7 days (n=5/group). Renal function, renal inflammatory/remodeling processes, and iRAS expression were evaluated. UUO increased plasma creatinine, right renal hypertrophy (9.08 ± 0.31, P<0.05 vs. Sham) and tubular dilatation in the left kidney cortex (42.42 ± 8.19µm, P<0.05 vs. Sham). This correlated with the increased mRNA of IL-1β (1.73 ± 0.14, P<0.01 vs. Sham, a pro-inflammatory cytokine) and TGF-β1 (1.76 ± 0.10, P<0.001 vs. Sham, a pro-fibrotic marker). In the renal cortex of the left kidney, UUO increased the mRNA and protein levels of renin (in 35% and 28%, respectively, P<0.05 vs. Sham). UUO decreased mRNA and protein levels for the (pro)renin receptor in the renal medulla (0.67 ± 0.036 and 0.88 ± 0.028, respectively. P<0.05 vs. Sham). Our results suggest that modulation of iRAS components depends on renal localization and occurs in parallel with remodeling and pro-inflammatory/pro-fibrotic mechanisms.